EFB battery

By using improved lead paste formula and partition structure in EFB batteries, the self-discharge and vulcanization problems of the battery during long-term parking is solved, which significantly improves the battery's cycle life and charging capacity, and extends the battery's service life.

CN119253088AActive Publication Date: 2025-01-03CAMEL GRP XIANGYANG BATTERY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411423308.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-03
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

Existing EFB batteries are prone to self-discharge, irreversible vulcanization and dendrite penetration during long-term parking, resulting in a shortening of battery life.

Method used

Using improved positive and negative lead paste formula, super fiber, carbon fiber, sodium hydroxymethylcellulose, sulfuric acid and other raw materials are added, and a silica coating and special rib structure are provided on the partition to improve the battery's Cycling life and charging acceptance capability.

Benefits of technology

It significantly improves the cycle life and charging acceptance ability of EFB batteries, reduces irreversible vulcanization and dendrites, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The EFB battery comprises a positive plate, a negative plate, a partition plate, electrolyte and a shell, the positive plate comprises a positive plate grid and positive lead plaster coated on the positive plate grid; the negative plate comprises a negative plate grid and negative lead plaster coated on the negative plate grid; the positive lead paste is prepared from the following raw materials in parts by weight: 95 to 105 parts of lead powder, 0.05 to 0.15 part of super-strong fiber, 0.05 to 0.2 part of carbon fiber, 0.2 to 0.4 part of carboxymethyl cellulose sodium, 8 to 10 parts of sulfuric acid and 9 to 11 parts of deionized water; the negative electrode lead paste is prepared from the following raw materials in parts by weight: 95 to 105 parts of lead powder, 0.05 to 0.15 part of super-strong fiber, 0.55 to 0.75 part of barium sulfate, 0.05 to 0.2 part of humic acid, 0.05 to 0.3 part of Norway lignin, 0.02 to 0.06 part of carbon black, 0.05 to 0.2 part of carbon fiber, 1.05 to 1.95 parts of an additive A, 0.05 to 0.2 part of an additive B, 0.02 to 0.05 part of ketjen black, 7 to 9 parts of sulfuric acid and 7.5 to 9.1 parts of deionized water. The partition plates are PE partition plates, vertical ribs are arranged on the positive electrode side, and tooth-shaped ribs are arranged on the negative electrode side. By improving the lead plaster and the partition plate, the service life of the battery is effectively prolonged, and the charging acceptance is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lead-acid batteries. Background Art

[0002] EFB battery is an enhanced flooded battery. Unlike lean battery, the remaining space is completely filled with sulfuric acid electrolyte after removing the plates, separators and other solid assembly parts in its tank. The electrolyte is in a surplus state, so it is called a "flooded" battery. It has the advantages of good low-temperature performance, low cost, mature production and recycling processes, etc. EFB battery is mainly used for start-stop vehicles. The function of the car start-stop system is to automatically shut down the car when waiting for traffic lights or long-term congestion, reducing fuel consumption and exhaust emissions caused by engine idling. However, frequent start-stop work is also a test of the performance and life of the battery. EFB battery can basically meet the requirements of the start-stop system for battery performance. However, the inventor found that there is a common vehicle use condition at present, that is, parking in a parking lot or underground garage for a long time, and starting the vehicle once every 15-30 days. The car is parked for a long time, which leads to self-discharge and over-discharge of existing EFB batteries, causing irreversible sulfidation of the battery, and even dendrite penetration, and serious attenuation of battery life. Therefore, a new type of EFB battery is urgently needed to solve the above problems. Summary of the invention

[0003] The object of the present invention is to overcome the above-mentioned deficiencies of the prior art and provide an EFB battery which can significantly improve the cycle life, charge acceptance and reduce irreversible sulfation.

[0004] The technical solution adopted by the present invention is: an EFB battery, comprising a positive plate, a negative plate, a separator, an electrolyte, and a shell; the positive plate comprises a positive grid and a positive lead paste coated on the positive grid; the negative plate comprises a negative grid and a negative lead paste coated on the negative grid; The positive electrode lead paste formula is made of the following raw materials in parts by weight: 95-105 parts of lead powder, 0.05-0.15 parts of super strong fiber, 0.05-0.2 parts of carbon fiber, 0.2-0.4 parts of sodium hydroxymethyl cellulose, 8-10 parts of sulfuric acid, and 9-11 parts of deionized water; The negative electrode lead paste formula is made of the following raw materials in parts by weight: 95-105 parts of lead powder, 0.05-0.15 parts of super strong fiber, 0.55-0.75 parts of barium sulfate, 0.05-0.2 parts of humic acid, 0.05-0.3 parts of Norwegian lignin, 0.02-0.06 parts of carbon black, 0.05-0.2 parts of carbon fiber, 1.05-1.95 parts of additive A, 0.05-0.2 parts of additive B, 0.02-0.05 parts of Ketjen black, 7-9 parts of sulfuric acid, and 7.5-9.1 parts of deionized water; The separator is a PE separator, with vertical ribs on the positive side and serrated ribs on the negative side; a silicon dioxide coating is provided on the positive side to improve the cycle life and charging acceptance of the battery. The separator wall thickness is 0.8±0.05mm.

[0005] The partition is a PE partition bag, the inner wall of the PE partition bag is provided with serrated ribs, the outer wall is provided with vertical ribs, and the outer wall is provided with a silicon dioxide coating; the wall thickness of the PE partition bag is 0.8±0.05mm.

[0006] The additive A is prepared by the following method: 0.1-0.3 parts of sodium hydroxymethyl cellulose and 0.05-0.15 parts of sodium stearate are weighed and mixed, dry-mixed for 3-5 minutes, added into 0.9-1.5 parts of deionized water, and ultrasonically dispersed for 20-30 minutes to obtain the additive A.

[0007] The additive B is prepared by the following method: 6±0.5 parts of sodium sulfate, 2±0.2 parts of potassium sulfate, and 2±0.2 parts of aluminum sulfate powder are mixed together by weight, and the mixture is stirred evenly to obtain the additive B.

[0008] The particle size of the potassium sulfate is 60-100 mesh; the particle size of the sodium sulfate is 80-200 mesh; and the particle size of the aluminum sulfate is 325-400 mesh.

[0009] The density of sulfuric acid in the positive lead paste and negative lead paste is 1.2-1.4 g / cm 3 .

[0010] The water content of the negative electrode lead paste is 10%-12%; the apparent density of the negative electrode lead paste is 4.4-4.6g / cm3; and the needle penetration of the negative electrode lead paste is 22-26mm.

[0011] The super strong fiber is a polyester fiber with a length of 2-3 mm and a diameter of 20±5 μm.

[0012] The negative electrode plate is prepared by the following method: (a) According to the negative electrode lead paste formula, the above raw materials are weighed; among them, Norwegian lignin, carbon fiber, carbon black, super fiber, humic acid, barium sulfate, and additive B are first mechanically premixed, and then dispersed in lead powder after being uniformly premixed, and dry-stirred to obtain a mixture; (b) Adding additive A to the mixture prepared in step (a), adding deionized water and stirring for 5-10 minutes; (c) Slowly adding sulfuric acid to the above system, controlling the system temperature between 30°C and 65°C during the acid addition process, and continuously stirring for 20-25 minutes throughout the process to prepare a negative electrode lead paste; (d) Use a small amount of deionized water to fine-tune the apparent density of the negative lead paste to 4.4-4.6 g / cm 3, needle penetration is 22-26mm; (e) Apply negative electrode lead paste to the negative electrode grid, and after curing and drying, a negative electrode plate is obtained.

[0013] The curing and drying adopts a medium-temperature and high-humidity curing process, wherein the curing time is 24-48 hours, the temperature is 50-55°C, and the relative humidity is 90-98%; the drying time is 24-36 hours, and the temperature is 50-60°C.

[0014] Compared with the prior art, the invention has the following beneficial effects: by adding additive A to the negative lead paste, sodium hydroxymethyl cellulose and sodium stearate work together, and due to their adsorption characteristics, they are adsorbed on the surface of the active material, have a bonding and reinforcing effect, enhance the bonding strength and conductivity between the active materials, prevent the generation of sulfation of the negative plate, thereby significantly improving the cycle life and charging acceptance, solving the problem of sulfation of the negative plate, and preventing the shrinkage of the active material of the negative plate. Additive B effectively inhibits the presence of lead ions in the electrolyte, thereby accelerating the precipitation rate of lead sulfate, and this rapid precipitation rate helps to prevent the formation of regular and dense large crystals, thereby inhibiting the growth of lead dendrites and avoiding short circuits between the plates; in addition, irregular small particles of lead sulfate are more easily restored to active materials during charging, further enhancing the performance and stability of the battery, and are conducive to reducing sulfation and reducing the generation of lead dendrites; at the same time, it can increase the real surface area of ​​the electrochemical reaction, reduce the resistance of the electrochemical reaction, improve the lead ion reduction reaction on the negative electrode surface, and improve the discharge capacity, active material utilization rate, and charging acceptance. The addition of a small amount of Ketjen Black improves the charge and discharge capacity of the battery. By improving the separator and its upper rib structure and adding a coating, the acid stratification is effectively improved, the battery sulfidation is slowed down, which is beneficial to prolonging the battery life and enhancing the charge acceptance capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Schematic diagram of the structure of the partition.

[0016] Figure 2 for Figure 1 AA section view. DETAILED DESCRIPTION

[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without carrying out creative work are within the scope of protection of the present invention.

[0018] Technologies, methods, and apparatus known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, such technologies, methods, and apparatus should be considered part of the authorization specification.

[0019] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.

[0020] like Figure 1 , Figure 2 As shown, the separator used in the present invention is a PE separator bag 1, the inner wall (negative electrode side) of the PE separator bag 1 is provided with serrated ribs 3, the outer wall (positive electrode side) is provided with vertical ribs 2, and a silicon dioxide coating is provided on the positive electrode side. Embodiment 1:

[0021] The EFB battery provided in this embodiment includes a positive plate, a negative plate, a separator, an electrolyte, and a shell; the positive plate includes a positive grid and a positive lead paste coated on the positive grid; the negative plate includes a negative grid and a negative lead paste coated on the negative grid. The separator used is a PE separator bag 1, and the PE separator bag 1 is provided with vertical ribs 2 on the outer wall, serrated ribs 3 on the inner wall, and a silicon dioxide coating on the inner wall. The wall thickness of the PE separator bag 1 is 0.8 mm.

[0022] Positive electrode lead paste formula: 100kg lead powder, 0.08kg super strong fiber, 0.2kg carbon fiber, 0.25kg sodium hydroxymethyl cellulose, 9.8kg sulfuric acid, 11kg deionized water.

[0023] Negative electrode lead paste formula: 100kg lead powder, 0.1kg super strong fiber, 0.6kg barium sulfate, 0.15kg humic acid, 0.15kg Norwegian lignin, 0.05kg carbon black, 0.15kg carbon fiber, 1.15kg additive A, 0.1kg additive B, 0.04kg Ketjen black, 8.4kg sulfuric acid, 9kg deionized water.

[0024] Additive A is prepared by the following method: 0.1 parts of sodium hydroxymethyl cellulose and 0.05 parts of sodium stearate are weighed and mixed, dry-mixed for 3-5 minutes, added into 1 part of deionized water, and ultrasonically dispersed for 20-30 minutes to obtain Additive A.

[0025] Additive B is composed of 60% sodium sulfate, 20% potassium sulfate, and 20% aluminum sulfate. The particle size of potassium sulfate is 60-100 mesh, the particle size of sodium sulfate is 80-200 mesh, and the particle size of aluminum sulfate is 325-400 mesh. Additive B is prepared by the following method: 6 parts of sodium sulfate, 2 parts of potassium sulfate, and 2 parts of aluminum sulfate powder are mixed together by weight, and stirred evenly to obtain additive B.

[0026] The super strong fiber is a polyester fiber with a length of 2-3mm and a diameter of 20±5μm.

[0027] Preparation of negative electrode plate: (a) according to the negative electrode lead paste formula, weigh the above raw materials; wherein Norwegian lignin, carbon fiber, carbon black, super fiber, humic acid, barium sulfate, and additive B are first mechanically premixed according to a proportion, and after the premixing is uniform, the whole is dispersed in lead powder and dry-stirred to obtain a mixture; (b) Adding additive A to the mixture prepared in step (a), adding deionized water and stirring for 5-10 minutes; (c) Slowly adding sulfuric acid to the above system, controlling the system temperature between 30°C and 65°C during the acid addition process, and continuously stirring for 20-25 minutes throughout the process to prepare a negative electrode lead paste; (d) Use a small amount of deionized water to fine-tune the apparent density of the negative lead paste to 4.4-4.6 g / cm 3 , needle penetration is 22-26mm; (e) Applying the lead paste to the negative electrode grid and curing and drying the lead paste to obtain the negative electrode plate. Embodiment 2:

[0028] The EFB battery provided in this embodiment includes a positive plate, a negative plate, a separator, an electrolyte, and a shell; the positive plate includes a positive grid and a positive lead paste coated on the positive grid; the negative plate includes a negative grid and a negative lead paste coated on the negative grid. The separator used is a PE separator bag 1, and the PE separator bag 1 is provided with vertical ribs 2 on the outer wall, serrated ribs 3 on the inner wall, and a silicon dioxide coating on the inner wall.

[0029] Positive electrode lead paste formula: 100kg lead powder, 0.08kg super strong fiber, 0.2kg carbon fiber, 0.25kg sodium hydroxymethyl cellulose, 9.8kg sulfuric acid, 11kg deionized water.

[0030] Negative electrode lead paste formula: 100kg lead powder, 0.1kg super strong fiber, 0.7kg barium sulfate, 0.15kg humic acid, 0.15kg Norwegian lignin, 0.05kg carbon black, 0.15kg carbon fiber, 1.25kg additive A, 0.15kg additive B, 0.04kg Ketjen black, 8.4kg sulfuric acid, 9kg deionized water.

[0031] Additive A is prepared by the following method: 0.15 parts of sodium hydroxymethyl cellulose and 0.1 parts of sodium stearate are weighed and mixed, dry-mixed for 3-5 minutes, added into 1 part of deionized water, and ultrasonically dispersed for 20-30 minutes to obtain Additive A.

[0032] Additive B is prepared by the following method: 6 parts by weight of sodium sulfate, 2 parts of potassium sulfate, and 2 parts of aluminum sulfate powder are mixed together, and the mixture is stirred evenly to obtain Additive B.

[0033] A negative electrode plate was prepared according to the negative electrode plate preparation method of Example 1. Embodiment 3:

[0034] The EFB battery provided in this embodiment includes a positive plate, a negative plate, a separator, an electrolyte, and a shell; the positive plate includes a positive grid and a positive lead paste coated on the positive grid; the negative plate includes a negative grid and a negative lead paste coated on the negative grid. The separator used is a PE separator bag 1, and the PE separator bag 1 is provided with vertical ribs 2 on the outer wall, serrated ribs 3 on the inner wall, and a silicon dioxide coating on the inner wall.

[0035] Positive electrode lead paste formula: 100kg lead powder, 0.08kg super strong fiber, 0.2kg carbon fiber, 0.25kg sodium hydroxymethyl cellulose, 9.8kg sulfuric acid, 11kg deionized water.

[0036] Negative electrode lead paste formula: 100kg lead powder, 0.1kg super strong fiber, 0.75kg barium sulfate, 0.15kg humic acid, 0.15kg Norwegian lignin, 0.05kg carbon black, 0.15kg carbon fiber, 1.35kg additive A, 0.2kg additive B, 0.04kg Ketjen black, 8.4kg sulfuric acid, 9kg deionized water.

[0037] Additive A is prepared by the following method: 0.2 parts of sodium hydroxymethyl cellulose and 0.15 parts of sodium stearate are weighed and mixed, dry-mixed for 3-5 minutes, added into 1 part of deionized water, and ultrasonically dispersed for 20-30 minutes to obtain Additive A.

[0038] Additive B is prepared by the following method: 6 parts by weight of sodium sulfate, 2 parts of potassium sulfate, and 2 parts of aluminum sulfate powder are mixed together, and the mixture is stirred evenly to obtain Additive B.

[0039] A negative electrode plate was prepared according to the negative electrode plate preparation method of Example 1.

[0040] Comparative Example:

[0041] Negative lead paste formula: 100kg lead powder, 0.1kg super fiber, 0.7kg barium sulfate, 0.15kg humic acid, 0.15kg Norwegian lignin, 0.05kg carbon black, 0.15kg carbon fiber, 0.04kg Ketjen black, 8.4kg sulfuric acid, 10kg deionized water. Negative lead paste and negative plate are made according to conventional process. Positive lead paste and separator are made by conventional technology.

[0042] The negative plates prepared in the above Examples 1-3 and the comparative example were made into EFB batteries of model 559064 (capacity: 59Ah; low temperature and high current discharge Icc 640A) according to conventional processes, and the battery performance was tested. The results are shown in Table 1.

[0043] 1. 20h rate capacity Detection method: Discharge at 2.95A in a 25℃±2℃ water bath, with a termination voltage of 10.5±0.05V, and record the discharge capacity.

[0044] 2. -18℃ low temperature detection Test method: Keep the temperature at -18℃±1℃ for not less than 24h. Discharge at 640A for 30s, and record the voltage at 10s and 30s. U10s>7.5V, U30s>7.2V are required.

[0045] 3. Static charging acceptance Test method: After the battery is fully charged, keep it in an ambient temperature of 25℃±2℃, discharge it at I0 for 5h, place it in an ambient temperature of 0℃±1℃ for 20h, charge the battery at a voltage of 14.4±0.10v in a low-temperature box, and record the charging current Ica at the 10th minute.

[0046] 4. Cycle life 50%DOD cycle test method: After the battery is fully charged, it is tested in a water bath at (40±1)℃. Perform the following cycle: Discharge at 5×I20 for 2 hours, disconnection standard: battery voltage ≤10V. Charge for 5 hours: limit voltage is 15.6V.

[0047] 17.5DOD% Cycle Test Method: The battery is fully charged and tested in a water bath at (26±1)℃. The battery is discharged at 4xI20 for 2.5 hours on a running rocking machine or in a water bath, and the following cycle is performed: charge at 7×I20 and (14.4±0.05)V for 40 minutes, and discharge at 7×I20 for 30 minutes. Disconnection standard: EFB battery is battery voltage ≤10V.

[0048] Table 1

[0049] The above description is only an exemplary embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An EFB battery, comprising a positive plate, a negative plate, a separator, an electrolyte, and a shell; the positive plate comprises a positive grid and a positive lead paste coated on the positive grid; the negative plate comprises a negative grid and a negative lead paste coated on the negative grid; characterized in that: The positive electrode lead paste formula is made of the following raw materials in parts by weight: 95-105 parts of lead powder, 0.05-0.15 parts of super strong fiber, 0.05-0.2 parts of carbon fiber, 0.2-0.4 parts of sodium hydroxymethyl cellulose, 8-10 parts of sulfuric acid, and 9-11 parts of deionized water; The negative electrode lead paste formula is made of the following raw materials in parts by weight: 95-105 parts of lead powder, 0.05-0.15 parts of super strong fiber, 0.55-0.75 parts of barium sulfate, 0.05-0.2 parts of humic acid, 0.05-0.3 parts of Norwegian lignin, 0.02-0.06 parts of carbon black, 0.05-0.2 parts of carbon fiber, 1.05-1.95 parts of additive A, 0.05-0.2 parts of additive B, 0.02-0.05 parts of Ketjen black, 7-9 parts of sulfuric acid, and 7.5-9.1 parts of deionized water; The separator is a PE separator, with vertical ribs on the positive electrode side and serrated ribs on the negative electrode side; the separator wall thickness is 0.8±0.05mm.

2. The EFB battery according to claim 1, characterized in that: The partition is a PE partition bag, the inner wall of the PE partition bag is provided with serrated ribs, the outer wall is provided with vertical ribs, and the outer wall is provided with a silicon dioxide coating; the wall thickness of the PE partition bag is 0.8±0.05mm.

3. The EFB battery according to claim 1, characterized in that: The additive A is prepared by the following method: 0.1-0.3 parts of sodium hydroxymethyl cellulose and 0.05-0.15 parts of sodium stearate are weighed and mixed, dry-mixed for 3-5 minutes, added into 0.9-1.5 parts of deionized water, and ultrasonically dispersed for 20-30 minutes to obtain the additive A.

4. The EFB battery according to claim 1, characterized in that: The additive B is prepared by the following method: 6±0.5 parts of sodium sulfate, 2±0.2 parts of potassium sulfate, and 2±0.2 parts of aluminum sulfate powder are mixed together by weight, and the mixture is stirred evenly to obtain the additive B.

5. The EFB battery according to claim 4, characterized in that: The particle size of the potassium sulfate is 60-100 mesh; the particle size of the sodium sulfate is 80-200 mesh; and the particle size of the aluminum sulfate is 325-400 mesh.

6. The EFB battery according to claim 1, characterized in that: The density of sulfuric acid in the positive lead paste and negative lead paste is 1.2-1.4 g / cm 3 .

7. The EFB battery according to claim 1, characterized in that: The water content of the negative electrode lead paste is 10%-12%; the apparent density of the negative electrode lead paste is 4.4-4.6g / cm 3 ; The needle penetration of the negative electrode lead paste is 22-26mm.

8. The EFB battery according to claim 1, characterized in that: The super strong fiber is a polyester fiber with a length of 2-3 mm and a diameter of 20±5 μm.

9. The EFB battery according to claim 1, characterized in that: The negative electrode plate is prepared by the following method: (a) According to the negative electrode lead paste formula, the above raw materials are weighed; among them, Norwegian lignin, carbon fiber, carbon black, super fiber, humic acid, barium sulfate, and additive B are first mechanically premixed, and then dispersed in lead powder after being uniformly premixed, and dry-stirred to obtain a mixture; (b) Adding additive A to the mixture prepared in step (a), adding deionized water and stirring for 5-10 minutes; (c) Slowly adding sulfuric acid to the above system, controlling the system temperature between 30°C and 65°C during the acid addition process, and continuously stirring for 20-25 minutes throughout the process to prepare a negative electrode lead paste; (d) Use a small amount of deionized water to fine-tune the apparent density of the negative lead paste to 4.4-4.6 g / cm 3 , needle penetration is 22-26mm; (e) Apply negative electrode lead paste to the negative electrode grid, and after curing and drying, a negative electrode plate is obtained.

10. The EFB battery according to claim 9, characterized in that: The curing and drying adopts a medium-temperature and high-humidity curing process, wherein the curing time is 24-48 hours, the temperature is 50-55°C, and the relative humidity is 90-98%; the drying time is 24-36 hours, and the temperature is 50-60°C.

Citation Information

Patent Citations

  • Super-capacitor lead acid battery cathode and preparation method thereof as well as super-capacitor lead acid battery comprising cathode

    CN103700822A

  • Low-temperature resistant negative lead paste of lead storage battery and preparation method of negative lead paste

    CN108598472A

  • Negative electrode lead paste and negative electrode plate of lead storage battery used at low temperature

    CN112786843A

  • Starting type lead-acid storage battery for commercial vehicle, negative electrode lead paste material and negative electrode plate

    CN115911289A

  • Hydrophobic substance of carboxymethylated cellulose nanofibers and manufacturing method thereof

    JP2019206607A